Ocular dryness in intensive care: proposal for a new nursing diagnosis - Jéssica Naiara de Medeiros Araújo; Ana Paula Nunes de Lima Fernandes; Ana Clara Dantas; Marcos Antonio Ferreira Júnior; Marcos Venícios de Oliveira Lopes; Allyne Fortes Vitor (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to analyze the concept associated with diagnostic proposition Ocular dryness in adult patients hospitalized in an Intensive Care Unit, identifying its attributes, antecedents and consequences. Methods: a methodological study carried out through concept analysis, operationalized by scoping review. Results: the analysis of 180 studies allowed the identification of two attributes, 32 antecedents and 12 consequences. The attributes were tear film deficiency and ocular signs and/or symptoms. The prevalent antecedents were incomplete eyelid closure (lagophthalmos) and blinking mechanism decrease. Major consequences included conjunctival hyperemia and decreased tear volume. Conclusions: this study allowed constructing nursing diagnosis Ocular dryness, part of domain 11, class 2, with 12 defining characteristics, 12 related factors, seven populations at risk and 13 associated conditions. This problem-focused proposal may provide targeted care by promoting early detection and implementing interventions that reduce the risk of ocular damage.